Making Ourselves Visible: Mobilizing Micro-Autoethnography in the Study of Self-Representation and Interface Affordances - McArthur, Victoria (Loading)

(untitled) (Canadian Game Studies Association, 2019)
Avatar customization and self-representation in games has been widely studied. In this paper, I propose the use of micro-autoethnography as a complementary methodology in such studies. I propose such an approach, theoretically and methodologically informed by Actor-Network Theory, as a way for researchers to situate themselves within their own studies of identity and play in games. I present a micro-autoethnographic study in which I, the researcher, attempt to create the same avatar in eight different Character Creation Interfaces (CCIs), otherwise known as a "trans-ludic" avatar. Implications for a micro-autoethnographic approach to avatar and identity research are discussed.